Reports on India's tax reforms - Kelkar, Vijay L.; Shome, Parthasarathi; Chelliah, Raja J.; Academic Foundation (New Delhi, India) (New Delhi : Academic Foundation : Economica India, 2003)
Reports on India's tax reforms with reference to the period 1991-2002.
Includes bibliographical references.
oif 01/09/15
Loan
Keywords: Taxation; Tax reforms; India